Camouflage [large type] - Pronzini, Bill (Pronzini, Bill. "Nameless Detective" mysteries., 2011)
Nameless may not like David Virden, but the case is simple enough: find his ex-wife - and they know where she is. Deliver some papers to her and it's all done. But she refuses the papers, sends a message to Virden never to contact her again, and slams the door. Virden threatens to sue, stops payment on his checks, and claims the woman they located isn't his wife. Then he disappears, and his fiancée hires Nameless to find out why. Clearly, someone is trying to make Nameless the monkey in the middle.